If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2p = 3p Solving 10 + -2p = 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 10 + -2p + -3p = 3p + -3p Combine like terms: -2p + -3p = -5p 10 + -5p = 3p + -3p Combine like terms: 3p + -3p = 0 10 + -5p = 0 Add '-10' to each side of the equation. 10 + -10 + -5p = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -5p = 0 + -10 -5p = 0 + -10 Combine like terms: 0 + -10 = -10 -5p = -10 Divide each side by '-5'. p = 2 Simplifying p = 2
| 3=44*333r | | x+y^2=100 | | 2.4x+4.2(2x)=2268 | | 4x+52=44 | | 3x-11(x/2-3/5)=2x-6(9/4-x/2) | | 3a+2b=1 | | 3x^4-9x^3-2x^2-6=0 | | 4x^2+25y^2-16x-50y-59=0 | | .5x+2.2=101 | | d-15=65 | | 3-4w=-2(w-5) | | 8(m+6)=15m-8 | | 6+3w=3(-w+11) | | 0.25z-22=-12 | | -23ba+a=17b | | 36x^2-33x-108=0 | | 27x^12y^10= | | 6n^2-168=18n | | 1.5y+10=1 | | -8k=24 | | x^2+12x-74=0 | | 12=10x-4-12x | | 10=t^2-8t | | 100s+20=460 | | A^2+23a-42=0 | | -8a(3-4b+7c)= | | 2(x-5)=4x-2(x+5)-1 | | 4*-z= | | H(t)=-16t^2+vt+h | | 5w+15=-3 | | 4*w= | | 11y-9y+15=11 |